IS CAPITAL STRUCTURE IMPORTANT FOR THE VALUE OF AGRO-FOOD CORPORATIONS IN SERBIA? - Janković-Perić, Marina; Jovanović, Dejan; Fedajev, Aleksandra (Economics of Agriculture, 2022)
The research aims to consider the nature of the influence of capital structure on the value of the corporations from the agro-food sector in Serbia. A panel regression analysis was used to test the hypotheses. The research covered the period from 2011 to 2018, and the sample consisted of 14 agro-food corporations whose shares are on the regulated market of the Belgrade Stock Exchange. The obtained results indicate that the capital structure has a statistically significant impact on the value of agro-food corporations and that the profitability of investment projects determines the nature of that impact. Consequently, the financial managers of agro-food corporations must consider the decision on the choice of capital structure as one of the key issues in the process of generating and increasing the corporation value.